Sistem Pemantauan Kualitas Air Budidaya Ikan Lele Menggunakan Teknologi IoT - Nurul Fahmi; Shellya Natalia (STMIK Budi Darma, 2020)
Water quality management plays an important role in catfish maintenance including piping, changing water, and using water filters. Temperature is a factor that affects the metabolic rate and solubility of gases in water. Higher temperatures will increase the metabolic rate of the fish so that respiration occurs faster. This can reduce the oxygen concentration in the water so that it can cause stress and even death in fish. The impact of stress causes the fish to decrease and then death occurs. A good temperature for the growth of catfish ranges from 25-32 degrees Celsius. The pH scale is 0-14 with a normal pH of 7, non-acidic and non-alkaline. The relationship between water acidity and fish life is very large. The point of death of fish at acidic pH is 4 and at alkaline pH is 11. In this study, a system for monitoring the quality of catfish culture water using Internet of Things (IoT) technology is proposed. The sensors used are Waterproof DSB180 temperature sensor and pH meter sensor. The results of temperature and pH measurements of catfish water will be displayed on the website and smartphone, making it easier for catfish farmers to control pH and temperature